Perlindungan Hukum Merek Asing Terkenal Yang Bergantung Pada Sistem Konstitutif Di Indonesia - Muhammad Lukman Fadillah; Nahrowi Nahrowi; Ipah Farihah (JOURNAL of LEGAL RESEARCH, 2022)
In order to improve the similarity of peoples to perform passing off reputation on the other side, now, therefore, mark breaching is especially motivated by a desire to gain benefit in the goods and services trade with the other mark which has been famous or popular or with the passing off owner mark or well-known mark. Trading of the trademark in well-known mark speed on selling to the market will undoubtedly profit quickly. The behavior in violation of the law harmed a company's reputation. With regard to the "EIK, EIKA, and EIKA brand" trademark issue, this journal seeks to discover how the "EIK" trademark is protected in Indonesia against well-known foreign marks that are not registered in Indonesia. A qualitative normative legal study employing a statute and case method. The statute used in this study is Law No. 20 of 2016 governing Marks and Geographical Indications, while the case used in this study is Supreme Court Decision No. 1300 K/Pdt.Sus-HKI/2017. The results of this study show that Law No. 20 of 2016 Governing Marks and Geographical Indications solely protects trademark rights based on registration. The Supreme Court judges gave substantial and correct consideration to the evidence in the case between the EIK brand and EIK, EIKA, and EIKA.